Vocational and Technical Education in Lebanon - Karam, Gebran (2006)
The current status of the Lebanese vocational and technical education (VTE) system is assessed and the strategic issues and challenges facing it are identified. In addition to the economic and social challenges that are common to many developing countries, the Lebanese system suffers from idiosyncratic problems, which may require innovative and bold reform strategies. The results of the first open consultations in the history of VTE with public and private sector stakeholders and key decision makers are analysed. These results are used to confirm the analysis of the current situation and to chart a strategic planning process for policy making, reform, and improved effectiveness in Lebanese vocational and technical education. (Contains 6 tables, 1 figure, and 1 footnote.)